Microprocessor controlled variation in cut-out pulse application in alternating current power - RINALDI VITO (2013)
A microprocessor operated controller device and associated method for modifying an AC input power to provide a reduced power AC output power to a load when coupled to the controller device. The AC output power has a series of cut-out pulses in each half cycle of the AC output power waveform. The device includes a switching system having a plurality of switching elements for positioning the series of cut-out pulses in each half cycle of a waveform of the AC input power to result in said reduced power AC output power and a switch control system for coordinating opening and closing of the plurality of switching elements during positioning of the series of cut-out pulses. The switch control system includes a synchronization system for synchronizing the switching system with timing of each half cycle of the AC input power waveform. The device also includes a digital processor for selecting a predefined pattern of the series of cut-out pulses from a plurality of predefined patterns of cut-out pulses, such that at least two patterns of the plurality of predefined patterns of cut-out pulses have different combinations of parameter definitions including number of cut-out pulses per half cycle and positioning of the pulses per half cycle.